Research progress on solid slow-release carbon source for enhancing wastewater nitrogen removal - XU Huchun; YANG Hui; YU Ting; ZHANG Junbo; CHEN Zhongtai; WANG Siya; SUN Yuxin; XU Guangjing (Gongye shui chuli)
In biological nitrogen removal denitrification for wastewater treatment, the scarcity of carbon sources often becomes a key factor limiting the efficiency of nitrogen removal. If this issue is not addressed properly, it can lead to total nitrogen in the effluent exceeding of legal emission limits, which would have adverse effects on the environment. To tackle this challenge, researchers have explored and utilized novel solid slow-release carbon sources as a potential alternative to traditional soluble carbon sources. Solid slow-release carbon sources have shown superior carbon supply characteristics compared to traditional carbon sources during the nitrogen removal process, which helps to improve the efficiency of nitrate removal. This paper aims to review different types of solid slow-release carbon sources, discuss their characteristics and performance in the denitrification process, and explore the challenges that may face in practical applications,such as controlling the release rate, environmental adaptability, cost-benefit analysis, and stability influencing factors. By overcoming these obstacles, the paper seeks to promote the sustainable development of wastewater treatment technologies, strengthen resource recycling, which not only helps to protect the environment but also conforms to China's overall strategy of promoting green development and building an ecological civilization.